Shariah Issues in Sukuk Mudarabah: A Criticism Against the Application of Repurchase Undertaking Arrangement - Mohd Sadad, Mahmud; Ibraheem Alani, Abdul Kareem (2019)
International Conference on Business and Management 2019 (ICBM2019) with the theme of "Reforming Business Management Towards IR 4.0". The conference aims to bring together leading academicians, researchers, scholars and students to exchange and share their experiences and researches on all aspects of business and globalization. It provides a premier interdisciplinary platform for researchers, practitioners, educators, and students to present and deliberate the most recent findings, trends, and concerns as well as practical challenges encountered and solutions adopted in the fields of business and management. ICBM2019 is proposed to be held at Universiti Sultan Zainal Abidin, Terengganu, Malaysia on 18 and 19 December 2019. The conference is to be hosted and organized by Faculty of Business and Management, Universiti Sultan Zainal Abidin, Terengganu, Malaysia. It is also jointly organized by Faculty of Islamic Economics and Finance, Universiti Islam Sultan Sharif Ali, (UNISSA), Brunei and Faculty of Economics and Business Islam (FEBI), The State Islamic University of Sunan Ampel Surabaya, Indonesia.